EFFECT OF THE GROWTH OF THE SERVICE SECTOR ON OPERATIONS MANAGEMENT IN A DEVELOPING ECONOMY - Kamoni, Peter; Kiarie, Dr. David (European Journal of Business and Strategic Management, 2018)
This document explores the concept of service and service sector in developing economies and shows that service sector has been growing and is equally important in the growth of their GDP, if not more important. Further, the paper elucidates the concept of service operation management in the context of service delivery and further shows the effect of growth of service sector on operations management. This research is informed on the theory of constraint and TQM. A review of literature on service operations management has also been done to further provide a deeper insight on the topic. Keywords: Growth, service sector, operations management